Information technology for management : driving digital transformation to enhance local and global performance, growth and sustainability - Turban, Efraim; Pollard, Carol (Carol E.); Wood, Gregory R. (2020)
"Preface To Be Updated-For castoff only Information Technology for Management discusses a variety of business strategies and explains how they rely on data, digital technology, and mobile devices to support them in the on-demand economy. Our goal is to provide students from any business discipline with a strong foundation for understanding the critical role that digital technology plays in enhancing business sustainability, profitability, and growth and excel in their careers. Enabling technologies discussed in this textbook include the following: Performance Combining the latest capabilities in big data analytics, reporting, collaboration, search, and digital communication helps enterprises be more agile and cuts costs to optimize business performance and profitability. Growth Strategic technologies enable business to create new core competencies, expand their markets, and move into new markets to experience exponential growth in the on-demand economy. Sustainability Cloud services are fundamental to sustaining business profitability and growth in today's on-demand economy. They play a critical role in managing projects and sourcing agreements, respecting personal privacy, encouraging social responsibility, and attracting and engaging customers across multimedia channels to promote sustainable business performance and growth. In this 11th edition, students learn, explore, and understand the importance of IT's role in supporting the three essential components of business performance improvement: technology, business processes, and people"--
Includes indexes.
Keywords: Management information systems